Leadership and Engagement - Tetley, Jessica Niamh Thomasina (2011)
Employees are extremely involved and tied closely to the organisation they work for which results in engagement sitting at the heart of establishments, proving itself to be a fundamental ingredient of organisational survival. When employees are engaged at work they perform better and are more devoted to carry out their role. Being able to inspire, motivate, support and develop employees with their charisma, emotional intelligence and self-assuredness is what gives leaders the capacity to be able to enrich engagement levels. Understanding the delicate balance of harmony in this relationship is crucial if organisations want to have an engaged workforce and thrive. The COVID-19 pandemic, in causing the move to online working has not only heightened the need for exceptional leadership but has challenged employee engagement. This study has qualitatively investigated how leadership has impacted employee engagement in the context of online working by conducting semi-structured, one-to-one interviews and thematically analysing the data collected. It was established that positive leadership does indeed have a positive impact upon engagement thus supporting research of previous academic literature. Positive attitudes of employee experiences of the leadership practice they were in contact with whilst working online were identified. Communication, adaptability, flexibility and understanding were highlighted as key leadership attributes that facilitated an environment where employees felt safe, supported and motivated to work whilst online ultimately boosting engagement levels. At a time where leadership and engagement were posed with the difficulty of overcoming the inability to be in the same room, the rapport and chemistry between managers and team members did not suffer because of the leadership philosophy that was being enacted. When the dynamism between the two concepts are fully understood and invested in, organisations have the chance to distinguish themselves within this new working world.